MRI in prostate cancer diagnosis: do we need to add standard sampling? A review of the last 5 years. Issue 4 (November 2018) - Stabile, Armando; Giganti, Francesco; Emberton, Mark; Moore, Caroline
Abstract Introduction In recent years, evidence has accrued to support the introduction of multiparametric magnetic resonance imaging (mpMRI) in the prostate cancer diagnostic pathway. The exact role of mpMRI in different settings is not widely agreed. In this review, we look at the use of MRI in three groups of men: biopsy naive men, those with a previous negative biopsy and those with a previous positive biopsy suitable for active surveillance. Material and methods An electronic MEDLINE/PubMed search up to 24th January 2018 was performed, using the search terms (prostate cancer OR prostate adenocarcinoma) AND (MRI OR magnetic resonance) AND (biopsy naive OR active surveillance OR prior negative biopsy OR no prior biopsy). Only those studies which reported detection rates of standard biopsy and MRI-targeted biopsy, where all men had both an MRI and standard biopsy were included. Results In total 34 articles were included (14 biopsy naive, 10 prior negative biopsy, and 10 prior positive biopsy). MRI-targeted biopsy consistently resulted in greater detection of clinically significant prostate cancer, and a lower detection of clinically insignificant prostate cancer, across all three patient populations. This effect was most prominent in men with at least one previous negative biopsy, and least prominent in men on active surveillance. In the presence of a negative mpMRI detection of csPCa found at systematic biopsy ranged from 0 to 20%. Conclusions MRI-targeted biopsy is more efficient than standard biopsy in detecting clinically significant disease in men with a positive MRI, and results in less detection of clinically insignificant cancer. In men with a negative MRI, a significant minority of men will have clinically significant cancer detected on systematic biopsy.